Changes on the Qualities of University Counsellors in China - Wen, Lan; Zheng, Peijue; Yang, Shaogang (ETHICS IN PROGRESS, 2018)
Counsellors are important key members in Chinese universities. In this paper, on the one hand, we compared student affairs workers’ occupational characteristics, classification and development of western as well as Chinese university. On the other hand, Chinese university faculty members and students are our subjects. Of 800 pieces circulated, 537 pieces are found to be effective. We verified the reliability and validity of data, then conducted correlation analysis, exploratory factor analysis (EFA), and confirmatory factor analysis (CFA). The test has good reliability and validity. Cronbach’s alpha coefficient and the split-half reliability coefficient are all above 0.9, indicating that the actual value is in good accordance with the true value. The internal alpha coefficient and the split-half reliability coefficient of each factor are all above 0.8. Χ2/df<5. GFI, AGFI, NFI, CFI, IFI,RMSEA and the other indicators are fitting, and this test meets measurement requirements. A 5-factor model is formulated based on the research results, including: moral quality; professional competence; political awareness; instructive ability; interpersonal skills. This 5-factor model reflects the evaluation of faculty members and students in universities on qualities of counsellors and transformation in their expectation for the role counsellors play as time goes by. So we summarize the qualities of counsellors are constantly changing. These changes have been constantly evolving in time, and their traits are such as: Objectivity of the times, Initiative of inner, Predictability of practice. Being well aware of the trend of this career is conducive to the formation of a sound relationship between counsellors and students, measurability for morality-oriented education, and improvement in counsellors’ overall qualities.